The risks of physicians' conformism: reflections from the opioid overflow - Luisa Cortellazzo Wiel; Giorgio Cozzi; Egidio Barbi (BMC, 2021)
Abstract Opioid-related mortality in adolescents is spreading in the US, with prescription opioids playing a crucial role in the development of addiction. We traced back to the process leading to the so called "opioid overflow", trying to identify any modifiable attitude. Since the late 1990s, pain was labelled as the "fifth vital sign" and its proper management was prompted, encouraging the use of opioids for any pain scored at a Numerical Rating Scale (NRS) of 7 or higher. This assumption has some remarkable limitations. NRS is a proxy of pain severity in children, and pain measurement should be strengthened by a more comprehensive pain evaluation. Moreover, while remaining a fundamental therapeutic right of patients suffering postoperative or chronic severe pain, opioids show no evidence of superiority respect to non-opioid regimens in the management of pain from several acute conditions. Italy, as other European countries, is often reluctant to the use of opioids, even when highly recommendable, missing the opportunity of properly treating those selected patients with severe pain. Both attitudes can be viewed as the result of an extreme simplification of the complex process of pain evaluation and treatment, by means of a 'one-size-fits-all' approach. This highlights the need for a systematic and patient-tailored attitude to children in pain, avoiding applying guidelines without question. Good clinical practice must rely on guidelines, which, however, as often based on partial and insufficient data, can be questioned by emerging new evidence, and should not substitute our rational thinking, and capability to understand each patient, avoiding excessive conformism.